2019
DOI: 10.1002/jcp.29087
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Silencing of keratin 1 inactivates the Notch signaling pathway to inhibit renal interstitial fibrosis and glomerular sclerosis in uremia

Abstract: Renal interstitial fibrosis is a key factor in the development of chronic renal diseases, possibly leading to uremia. The present study conducted aimed to assess the hypothesis whether keratin 1 (KRT1) silencing could suppress kidney interstitial fibrosis and glomerular sclerosis via the Notch pathway to alleviate uremic symptoms. Differentially expressed genes associated with uremia were identified using the gene expression omnibus (GEO) database. Uremic rat models were established, in which short hairpin-RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Some scholars found that the expressions of Notch1 and Jagged1 were significantly upregulated in the kidney tissues of IgA nephropathy, and Notch1, HEY1, and HES1 were significantly reduced after administration of the Notch1 pathway inhibitor DAPT, thereby alleviating RIF [ 49 ]. Notch pathway inhibitors were found to weaken glomerulosclerosis and RIF by decreasing the expression of Jagged1, Notch1, NICD1, HEY1, HES1 α -SMA, and fibronectin in uremic rats [ 50 ]. Thus, inhibition of the Notch pathway can alleviate RIF to a certain extent.…”
Section: Discussionmentioning
confidence: 99%
“…Some scholars found that the expressions of Notch1 and Jagged1 were significantly upregulated in the kidney tissues of IgA nephropathy, and Notch1, HEY1, and HES1 were significantly reduced after administration of the Notch1 pathway inhibitor DAPT, thereby alleviating RIF [ 49 ]. Notch pathway inhibitors were found to weaken glomerulosclerosis and RIF by decreasing the expression of Jagged1, Notch1, NICD1, HEY1, HES1 α -SMA, and fibronectin in uremic rats [ 50 ]. Thus, inhibition of the Notch pathway can alleviate RIF to a certain extent.…”
Section: Discussionmentioning
confidence: 99%
“…The observation of KRT10 expression in every tissue within the GTEx database is in agreement with numerous prior reports of expression in skin [ 55 ], breast [ 56 ], testis [ 57 ], cervix [ 58 ], thymus [ 59 ] and vagina [ 60 ]; and with the finding that expression of a transgene driven by the KRT10 promoter was observed in stomach, small intestine, cecum, colon, spleen, and pancreas [ 61 ]. While KRT1 expression is well established in skin integrity [ 55 , 62 ], colonic mucosa [ 63 ], kidney [ 64 ] and vagina [ 65 ], the GTEx data indicate that KRT1 has a much more expansive expression pattern than is suggested by the literature. These expression data also raise the question as to whether KRT10 is expressed in terminally-differentiated epithelial cells [ 66 ].…”
Section: Main Textmentioning
confidence: 99%